2001
DOI: 10.1063/1.1368865
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and phase transitions of epitaxial tin oxide thin films on (1̄012) sapphire

Abstract: Articles you may be interested inGaN epitaxial films grown by hydride vapor phase epitaxy on polycrystalline chemical vapor deposition diamond substrates using surface nanostructuring with TiN or anodic Al oxide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
85
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 16 publications
15
85
0
Order By: Relevance
“…This combination has been shown to enhance sensor sensitivity, attributed to the presence of p−n junctions due to having the p-type SnO semiconductor mixed with n-type SnO2. 22 Similar behavior has also been noted in the case of mixtures of p-type CuO with n-type SnO2. 23 Although there has been little work reported on systematic efforts to synthesize and optimize SnO/SnO2 for potential sensor applications, our previous study 24 has shown that nanocrystalline mixed Sn(II)/Sn(IV) oxide powders can easily be synthesized from SnCl2 precursor by a modified sol−gel technique.…”
Section: Introductionsupporting
confidence: 68%
“…This combination has been shown to enhance sensor sensitivity, attributed to the presence of p−n junctions due to having the p-type SnO semiconductor mixed with n-type SnO2. 22 Similar behavior has also been noted in the case of mixtures of p-type CuO with n-type SnO2. 23 Although there has been little work reported on systematic efforts to synthesize and optimize SnO/SnO2 for potential sensor applications, our previous study 24 has shown that nanocrystalline mixed Sn(II)/Sn(IV) oxide powders can easily be synthesized from SnCl2 precursor by a modified sol−gel technique.…”
Section: Introductionsupporting
confidence: 68%
“…In a recent work, Seko 12 used first-principles techniques and cluster expansion to calculate the most probable structure for these intermediary systems obtaining consistent data with powder diffraction. However, electron and optical properties data are still missing due to the difficulties in synthesis and in the design of devices using Sn 3 4 , which in turn, decomposes into SnO 2 and metallic tin. In this way, when the oxireduction process is controlled, this nonstoichiometric compound should be grown.…”
Section: Introductionmentioning
confidence: 99%
“…3 The intermediary and nonstoichiometric SnO 2−x ͑0 Ͻ x Ͻ 1͒ compounds are hardly synthesized and the fewer experimental observations are only a result of nonintentional thermal oxidation of SnO and SnO 2 phases. 4,5 Sn 3 O 4 is a good example of a nonstoichiometric structure that deserves attention. It was first identified by Lawson 6 as a result of oxidation of another nonstoichiometric phase, SnO.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, few reports has been cited to investigate the micro-structural and electrical properties of SnO [8,9]. The SnO has been marked as anode material [10] and has been employed for other applications such as for gas sensitive material [11], coating substance [12], catalyst [12], precursor for the production of tin dioxide [13],and for p-channel thin film transistor [14,15]. The reported crystal habit of SnO is tetragonal crystal structure which is similar to that of the 'red' (a or litharge) modification of isovalent PbO [16].…”
Section: Introductionmentioning
confidence: 99%